Prevalence of Speech and Language Disorders in Children Presenting to a Tertiary Care Center: Prevalence of Speech and Language Disorders in Children - Aftab, Kausar; Afzal, Erum; Maqsood, Imran; Tabassum, Rukhsana; Ishfaq, Hafiz Muhammad (Pakistan Journal of Health Sciences, 2025)
Speech and language disorders (SLDs) are among the most common developmental challenges in children. While some children may experience only a speech disorder or a language disorder. Objective: To determine the prevalence of SLDs in children presenting to a tertiary childcare hospital in South Punjab, Pakistan. Methods: This cross-sectional study was conducted at the Developmental and Behavioural Pediatric Department, The Children’s Hospital and Institute of Child Health, Multan. A sample size of 300 was calculated. Children aged 2 to 16 years were analyzed. Non-probability, a convenient sampling technique was adopted. Socio-demographic data, including gender, age, residence and socio-economic status, were collected, and SLDs were identified. SLDs were correlated with gender and age groups, applying a chi-square test (p<0.05 considered significant). Results: 12,055 (81.0%) had SLDs, with a male predominance (8441, 70.0%). The mean age was 5.04 ± 2.69 years. The most common SLDs were global developmental delay (GDD) (31.3%), cerebral palsy (17.3%), intellectual disability (17.0%), and autism spectrum disorder (ASD) (11.2%). GDD (34.1% vs. 30.1%, p<0.001), cerebral palsy (18.3% vs. 16.8%, p<0.001), and hearing loss (4.2% vs. 1.9%, p<0.001) were more common in females, while ASD (12.3% vs. 8.6%, p<0.001) and stammering (5.3% vs. 3.1%, p<0.001) were more common in male. GDD and ASD were more prevalent in younger children (p<0.001), while cerebral palsy and articulation disorders were more common in older children (p<0.001). Conclusions: The prevalence of SLDs among children visiting the developmental and behavioural pediatric outpatient department of a tertiary childcare setting is very high, particularly among male, and younger children.